Behavioral adaptations and coexistence of the five-striped palm squirrel (Funambulus pennantii) in urban Kathmandu, Nepal (Our Nature, 2025)
The coexistence between humans and wildlife began since their origin sharing foods and habitats. Urban areas are human-dominated, non-natural, and non-protected environments where wildlife struggles to survive. Despite life-threatening issues persisted in these places, five-striped palm squirrel (Funambulus pennantii Robert Charles Wroughton) inhabit in dense human dwellings. Therefore, we aimed to study nine types of behaviors (i.e. adaptive, aggressive, avoidance, cognitive, feeding, grooming, reproductive, social and aestivation) in Shahid Gangalal Heart Centre (SGHC), HAMS Hospital and their surroundings at Kathmandu by visual observation (VO) and hearing sound calls (HSC). During study, visits were made twice in each site in all seasons (i.e. winter, spring, summer, and autumn), and documented every sign or signal that offers value for survival. Food availability rather than food variety, temperature and precipitation was the major determinant factor for occurrence in the habitat. Although agnostic behavior shaped their hierarchies within the species, avoidance and adaptation were the key behaviors to keep them survive in human dominated expanses. The most preferred nutrient was the leaf buds (27.9%, n=12) and insects as the least (4.7%, n=2). Although tree branches and trunks were the most preferred substrates (51.8%, n=29) for roosting and safety, their diurnal activities and vocalization drew human attention and provoked nearby stray dogs creating risks. Conclusively, squirrels were found to co-exist under prominent conflicts with humans and dogs in shared territories. So, further study is recommended to understand effects of pollution in reproduction and transmission of zoonotic diseases.